1990
DOI: 10.1111/j.1651-2227.1990.tb11550.x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effects on Lung Function of Instilled Human Surfactant in Mechanically Ventilated Newborn Infants with IRDS

Abstract: We have studied the effects on lung volume, respiratory mechanics and ventilation during the first hours after instillation of 60 mg/kg of human surfactant into the trachea of 4 very preterm, newborn infants with severe IRDS under mechanical ventilation. Measurements were made with a "face-out" body plethysmograph and a modified nitrogen wash-out method. In addition to a transient decrease in total and alveolar ventilation immediately after the instillation we found an immediate rise in lung volume, but respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
2

Year Published

1992
1992
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 17 publications
7
32
2
Order By: Relevance
“…Only a limited number of studies of pul monary mechanics after surfactant instilla tion in preterm newborn infants have been published [6][7][8][9], One study showed improve ment in tidal minute volume and dynamic compliance after bovine surfactant instilla tion during spontaneous respiration but not during mechanical ventilation [6]. Another study found no significant changes in dy namic compliance until 24 h after surfactant instillation [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a limited number of studies of pul monary mechanics after surfactant instilla tion in preterm newborn infants have been published [6][7][8][9], One study showed improve ment in tidal minute volume and dynamic compliance after bovine surfactant instilla tion during spontaneous respiration but not during mechanical ventilation [6]. Another study found no significant changes in dy namic compliance until 24 h after surfactant instillation [7].…”
Section: Discussionmentioning
confidence: 99%
“…A recent report on the effect of rescue doses of artificial surfactant (Exosurf) showed improvement in respiratory system static compliance only 1 week after surfactant instillation [8], These studies failed to show any change in lung mechanics during the first hours after surfactant treatment. However, re cently Edberg et al [9] studied the effects of instillation of human surfactant in 4 preterm infants with severe RDS during mechanical ventilation using a body plethysmograph and a modified nitrogen washout method. These authors found an immediate rise in lung vol ume with an increase in FRC of 20-120% within 15 min.…”
Section: Discussionmentioning
confidence: 99%
“…[12] 1990 15 min 4 -■ » G jy n increase in FRC Goldsmith ct al. [14] 1991 1 h 7 -» C d y n increase in FRC Svcnningsen et al [15] 1992 24 h 8 Î C " increase in FRC Bhutani et al [9] 1992 1 h 32^ C d y n not measured Phenningcr ct al.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in BP may be related to the rapid recniitment of atelectatic areas by surfactant treatment [21,22], possibly leading to a de crease in the pulmonary vascular resistance and, consequently, to an increase in left-toright shunting through the ductus arteriosus [11], Also a decrease in peripheral vascular resistance as described by Skov et al [10] and by Cowan et al [9] may lead to a transient drop in BP. CBFVs may also be subject to variations in PCO2.…”
Section: Resultsmentioning
confidence: 99%